If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + 1) = 2(x + 11) Reorder the terms: 8(1 + x) = 2(x + 11) (1 * 8 + x * 8) = 2(x + 11) (8 + 8x) = 2(x + 11) Reorder the terms: 8 + 8x = 2(11 + x) 8 + 8x = (11 * 2 + x * 2) 8 + 8x = (22 + 2x) Solving 8 + 8x = 22 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 8 + 8x + -2x = 22 + 2x + -2x Combine like terms: 8x + -2x = 6x 8 + 6x = 22 + 2x + -2x Combine like terms: 2x + -2x = 0 8 + 6x = 22 + 0 8 + 6x = 22 Add '-8' to each side of the equation. 8 + -8 + 6x = 22 + -8 Combine like terms: 8 + -8 = 0 0 + 6x = 22 + -8 6x = 22 + -8 Combine like terms: 22 + -8 = 14 6x = 14 Divide each side by '6'. x = 2.333333333 Simplifying x = 2.333333333
| 2+(4+2k)+10=k | | 5x+2=2(2x+1)+x | | x^6-27y^9z^3=0 | | 6x+7=4x+11 | | 5y-3+7-2y=16 | | 18x-14-21x=17-x+7 | | 10.4-1.3b+3.7b=-5.2 | | -x^2+3x=-4x+6 | | 4x+3x^2-3x= | | 4+9x^2-12x=0 | | 12+2n=9(n-7)-2 | | i+6i=7 | | .5x+4=-.33x+.5 | | 0.5x-2.325=3.95 | | X=10(x-.50)+9 | | 9-4x-4=x+7-1 | | 15=4(6-3c) | | 3x+4=(7-4)6x-4x | | 63+30+2x+7=180 | | 1.5(4x-3)=2(0.5x-3.5) | | 4x-46=38 | | 16x+5-3=-2x-15 | | 24-5x=17+2x | | H(x)=0.75+18*(x) | | 2x-7y+6=3(y-x)-4 | | 2(x-4)=-5 | | 3(2-4)=6(-2) | | 5d+6n=t | | (0)-3y=6 | | -1x-4=4 | | d-(-3)=100 | | -43=7-8t |